Jesus and scripture : studying the New Testament use of the Old Testament - Moyise, Steve (Grand Rapids, MI : Baker Academic, 2011)
"Steve Moyise's Jesus and Scripture begins with concise assessments of how Jesus used and understood Old Testament Scripture in the four respective New Testament Gospels. Moyise then surveys opinions on the subject from a range of scholars, from those who think Jesus made little or no use of Scripture to those who think that Jesus made extensive use of Scripture. This excellent book strikes the right balance and brings clarity to a subject that is often discussed in convoluted and confusing ways. Its value for students is obvious, but veteran scholars will also find it very helpful"--Craig A. Evans, Payzant Distinguished Professor of New Testament, Acadia Divinity College
Introduction -- Jesus and scripture according to Mark's Gospel -- Jesus and scripture according to Matthew's Gospel -- Jesus and scripture according to Luke's Gospel -- Jesus and scripture according to John's Gospel -- Jesus and scripture : minimalist views -- Jesus and scripture : moderate views -- Jesus and scripture : maximalist views
Reprint. Originally published: London : SPCK, 2010
Includes bibliographical references (pages 138-140) and indexes
Keywords: Jesus Christ -- Views on the Old Testament; Jesus Christ -- Biblical teaching; Bible. -- Relation to the Old Testament; Bible. -- Quotations in the New Testament; Bible. -- Criticism, interpretation, etc; Intertextuality in the Bible